Electrocatalytic Production of Hydrogen Peroxide with Poly(3, 4‐ethylenedioxythiophene) Electrodes. (30th October 2018) - Mitraka, Evangelia; Gryszel, Maciej; Vagin, Mikhail; Jafari, Mohammad Javad; Singh, Amritpal; Warczak, Magdalena; Mitrakas, Manassis; Berggren, Magnus; Ederth, Thomas; Zozoulenko, Igor; Crispin, Xavier; Głowacki, Eric Daniel
Abstract: Electrocatalysis for energy‐efficient chemical transformations is a central concept behind sustainable technologies. Numerous efforts focus on synthesizing hydrogen peroxide, a major industrial chemical and potential fuel, using simple and green methods. Electrochemical synthesis of peroxide is a promising route. Herein it is demonstrated that the conducting polymer poly(3, 4‐ethylenedioxythiophene), PEDOT, is an efficient and selective heterogeneous catalyst for the direct reduction of oxygen to hydrogen peroxide. While many metallic catalysts are known to generate peroxide, they subsequently catalyze decomposition of peroxide to water. PEDOT electrodes can support continuous generation of high concentrations of peroxide with Faraday efficiency remaining close to 100%. The mechanisms of PEDOT‐catalyzed reduction of O2 to H2 O2 using in situ spectroscopic techniques and theoretical calculations, which both corroborate the existence of a chemisorbed reactive intermediate on the polymer chains that kinetically favors the selective reduction reaction to H2 O2, are explored. These results offer a viable method for peroxide electrosynthesis and open new possibilities for intrinsic catalytic properties of conducting polymers. Abstract : The conducting polymer PEDOT is a robust electrocatalyst for efficient electrochemical production of hydrogen peroxide (H2 O2 ) via cathodic reduction of oxygen.